THE HOLY MOUNTAIN SALKANTAY: LANDSCAPE, POWER AND ANCESTORS - Bolívar Yapura, Wilber (2013)
For the people of the Andes, the Apus reverence and sacred mountains, converted into local protectors, did not go unnoticed at the time, so, as the Salkantay mountains, including the surrounding ones, assume an important role into the Andean worldview. For example the Waqay Willke snowy peak (5720 m), within the traditional Andean symbolism of dualistic thinking, is considered the complement of Salkantay, that is one of the most powerful and active deities of the place, and it is appreciated by the people, the father of all the mountains in the region and even nowadays is held in great veneration, so Machupicchu and Choquechurco holds an intimate visual contact with the Salkantay and other snowy peaks of the Vilcabamba chain.